Real time evaluation of an air leak into a dry etching equipment by means of optical emission spectroscopy: evaluation and results in high volume production regime - Ciovacco, F.; Alba, S.; Fazio, G.; Somboli, F. (Advanced Semiconductor Manufacturing Conference and Workshop, 2003 IEEEI/SEMI, 2003)
Chamber leak test is one of the most important tests that are performed on plasma reactors for etch, CVD, etc. Optical Emission Spectroscopy OES is a powerful non-invasive tool to perform real time plasma diagnostic and in theory could be use as an alternative method to evaluate the air leak into the plasma reactor. The idea is to detect and quantify small differences in the emission spectrum of the plasma when a presence of a quantity of air is higher than the tolerated threshold. This would give the possibility to test the level of the leak chamber any time automatically during production or between wafers and hence to increase the frequency of testing. In this presentation we describe not only the method itself with the instrument set up and the test configuration adopted but also the experience acquired in high volume production regime and the numerous advantages obtained in comparison with the conventional leak rate test.